2010
DOI: 10.1038/nn.2621
|View full text |Cite
|
Sign up to set email alerts
|

Narp regulates homeostatic scaling of excitatory synapses on parvalbumin-expressing interneurons

Abstract: Homeostatic synaptic scaling alters the strength of synapses to compensate for prolonged changes in network activity, and involves both excitatory and inhibitory neurons. The immediate-early gene termed Narp (Neuronal activity-regulated pentraxin) encodes a secreted synaptic protein that can bind and cluster AMPA receptors (AMPARs). Here, we report that Narp prominently accumulates at excitatory synapses on Parvalbumin-expressing interneurons (PV-INs). Increasing network activity results in a homeostatic incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
275
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(302 citation statements)
references
References 46 publications
(72 reference statements)
9
275
4
Order By: Relevance
“…In dissociated cortical cultures it has been shown that excitatory synapses onto excitatory pyramidal neurons are scaled up by activity blockade, whereas excitatory synapses onto GABAergic interneurons are not ). On the other hand, enhancing network activity does increase excitatory transmission onto GABAergic interneurons Chang et al 2010), which should promote the recruitment of additional inhibition when activity in a circuit increases. Further, it has been shown both in vitro and in vivo that inhibitory synapses onto pyramidal neurons are regulated in the opposite direction from excitatory synapses in response to a drop in activity or sensory drive (Kilman et al 2002;Vale and Sanes 2002;Maffei et al 2004;Hartman et al 2006;Huupponen et al 2007).…”
Section: Specificity Of Synaptic Scaling Rules For Synapse Typementioning
confidence: 99%
“…In dissociated cortical cultures it has been shown that excitatory synapses onto excitatory pyramidal neurons are scaled up by activity blockade, whereas excitatory synapses onto GABAergic interneurons are not ). On the other hand, enhancing network activity does increase excitatory transmission onto GABAergic interneurons Chang et al 2010), which should promote the recruitment of additional inhibition when activity in a circuit increases. Further, it has been shown both in vitro and in vivo that inhibitory synapses onto pyramidal neurons are regulated in the opposite direction from excitatory synapses in response to a drop in activity or sensory drive (Kilman et al 2002;Vale and Sanes 2002;Maffei et al 2004;Hartman et al 2006;Huupponen et al 2007).…”
Section: Specificity Of Synaptic Scaling Rules For Synapse Typementioning
confidence: 99%
“…Additional sharpening of plasticity at the circuit level is provided by differential expression of long-term plasticity (either LTP or LTD, both forms or neither form) at excitatory inputs with specific populations of inhibitory (GABA) interneurons (Chang et al 2010;Nissen et al 2010;Sarih et al 2012). The selective expression of long-term plasticity at these inputs can reduce potential excitotoxic consequences of the activity-dependent plasticity mediating learning and memory expressed by the neurons of the circuit encoding the memory (Lamsa et al 2007;Isaacson and Scanziani 2011).…”
Section: Local Expression Of Zero-sum Long-term Plasticitymentioning
confidence: 99%
“…At the wider network level, mechanisms that impact on more global changes, such as the balance of excitatory and inhibitory synaptic inputs, could restrain overall excitability to more acceptable levels (Chang et al 2010;Isaacson and Scanziani 2011;Campanac et al 2012).…”
mentioning
confidence: 99%
“…HSP mechanisms stabilize neural networks by policing overall neuronal activity and adjusting synaptic strength accordingly to achieve the desired compensatory change [2]. For instance, sustained increases in network activity initiate molecular cascades that weaken excitatory and strengthen inhibitory synapses [6,7], whereas chronic decreases in activity provoke the opposite synaptic adjustments, thus strengthening excitatory synapses while weakening inhibitory ones [6,8]. Therefore, homeostatic plasticity is thought to maintain neuronal activity within a suitable range that supports normal function.…”
Section: Hsp In Epilepsy: Trying Too Hard?mentioning
confidence: 99%